Sensitivity of native and alien freshwater bivalve species in Europe to climate‐related environmental factors. Issue 5 (14th May 2018) - Collas, Frank P. L.; Buijse, Anthonie D.; Hendriks, A. Jan; van der Velde, Gerard; Leuven, Rob S. E. W.
Abstract: While native freshwater bivalve species are declining, several alien bivalve species have become invasive, thereby impacting ecosystem functioning and services. These biodiversity changes can be attributed to deteriorated water quality, hydro‐morphological alterations, and the overarching effect of global change. Therefore, a systematic assessment of the sensitivity of freshwater bivalve species nowadays occurring in European inland waters to environmental factors is urgent. The present study reviewed 493 relevant papers, resulting in 8405 data entries on presence–absence of bivalve species in relation to environmental factors that are affected by global change (i.e., water temperature, water depth, oxygen availability, and flow velocity). From these worldwide field data, minimum and maximum values measured in their habitat and water bodies were selected. In addition, data on laboratory‐derived tolerance ranges were collected. Subsequently, novel species sensitivity distributions (SSDs) were derived for each environmental factor using field‐based occurrence data and laboratory‐derived tolerance ranges, respectively. Species sensitivity distributions for maximum habitat temperature significantly differed between native and alien species. The latter occurred in habitats with higher maximum water temperatures than native species. The increase in water temperatures by global warming will affect a higher percentage of native species than alien species. The ranking of species based on their sensitivity for various environmental factors shows that vulnerable and endangered species have a higher overall sensitivity and are likely to be more affected by climate change. Invasive alien species were found to have a lower overall sensitivity and are thus less affected by climate change further aiding to their invasive nature. The available SSDs allow the ranking of freshwater bivalve species sensitivity to environmental stressors, the prediction of their potential occurrence in freshwater habitats, and the evaluation of management measures to optimize their biodiversity and ecosystem services.